Ultra-small micelles based on polyoxyl 15 hydroxystearate for ocular delivery of myricetin: optimization, in vitro, and in vivo evaluation - Yuzhen Hou; Fan Zhang; Jie Lan; Fengyuan Sun; Jun Li; Mengshuang Li; Kaichao Song; Xianggen Wu (Taylor & Francis Group, 2019)
The aim was to develop a nanocarrier based on polyoxyl 15 hydroxystearate (Kolliphor® HS15, HS15) micelles for the solubility, stability, and ocular delivery of myricetin (Myr). An optimized ratio of HS15 and Myr was prepared to fabricate HS15-Myr micelle ophthalmic solution. Myr-encapsulating HS15 micelles (HS15-Myr micelles) were subjected to physicochemical characterizations. The chemical stability of Myr in HS15 micelles and storage stability of HS15-Myr micelle ophthalmic solutions were evaluated. In vitro parallel artificial membrane permeability assay and antioxidant activity of Myr in HS15 micelles were also measured. In vivo ocular tolerance, corneal permeation, and anti-inflammatory efficacy studies were conducted following ocular topical administration. HS15-Myr micelles were successfully prepared and presented transparent appearance with high encapsulation (96.12 ± 0.31%), ultra-small micelle size (a mean diameter of 12.17 ± 0.73 nm), uniform size distribution (polydispersity index [PDI] = 0.137 ± 0.013), and negative surface charge (− [4.28 ± 0.42] mV). Myr in HS15 micelle solution demonstrated higher aqueous stability than the free Myr solution among the accepted pH range for eyedrops. HS15-Myr micelle ophthalmic solution demonstrated high storage stability at 4 °C and 25 °C. HS15 micelles could significantly improve in vitro antioxidant activity and faster membrane permeation of Myr. No irritations or corneal damage were revealed in rabbit eyes after ocular administration of HS15-Myr micelle solution. In vivo corneal permeation study demonstrated that HS15-Myr micelles could penetrate the cornea efficiently in mouse eyes. Further, HS15-Myr micelles also demonstrated significant in vivo anti-inflammatory activity. It can be concluded that HS15 micelles are a potential ophthalmic delivery nanocarrier for poorly soluble drugs such as Myr.